Factors related to Quality of Work Life among Nurses, Tertiary Level Hospitals, People's Republic of Bangladesh. (December 2016) - Akter, N.; Akkadechanunt, T.; Chontawan, R.; Klunklin, A.
Abstract : Background: Quality of work life is important for hospital employees including nurses as it affects safety and quality care for patients as well as organizational factors. Objective: To examine the level of quality of work life and examine the relationship between personal factors, organizational factors and quality of work life among nurses in tertiary level hospitals, People's Republic of Bangladesh Methods: Descriptive correlational study design was conducted with 288 nurses, randomly selected from six tertiary level hospitals in Bangladesh. The research instruments consist of Quality of Nursing Work Life Survey, Expanded Nursing Stress Scale, Questionnaire of Organizational Commitment, and Practice Environment Scale of the Nursing Work Index which were translated into Bengali using back translation process. The content validity of each instruments were confirmed by the developers and reliability of Quality of Nursing Work Life Survey, Expanded Nursing Stress Scale, Questionnaire of Organizational Commitment, and Practice Environment Scale of the Nursing Work Index were 0.94, 0.95, 0.84, and 0.90 respectively. Data were analyzed by Pearson Product Moment statistics. Results: The result found that nurses working in tertiary level hospital, People's Republic of Bangladesh perceived their quality of work life at moderate level. Personal factors include years of experience, years of education, and monthly income were statistically significant positively related to quality of work life (r = 0.50, 39, and 0.17 respectively). Organizational factors include organizational commitment and nursing practice environment were statistically significant positively related to quality of work life (r = 0.66 and 0.74) and job stress was found statistically significant negatively related quality of work life (r = −0.46). Conclusion: Nurse administrators can use the findings of the study to develop policies and strategies to manage the quality of work life among nurses working in tertiary level hospitals. Priority of intervention for improving quality of work life among nurses will be designed based on the personal and organizational factors that are related to quality of work life among Bangladeshi nurses.